2013
DOI: 10.1016/s0325-7541(13)70021-x
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic tolerance of cyanobacterial strains with potential use in biotechnology

Abstract: The arsenic content of various water bodies in Argentina is higher than the acceptable levels for human and animal uses. Cyanobacteria are widely distributed in aquatic environments and can bioaccumulate arsenic (As). This study presents the response of indigenous cyanobacteria to As(III) and As(V), including the species Tolypothrix tenuis, Nostoc muscorum and Nostoc minutum, previously used with biotechnological purposes. As(III) resulted more toxic than As(V) in all cases, causing cell death in the range of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…As (III) showed more toxicity (~100 times) to Synechocystis cells than As (V) ( Figure 1 , Supplementary Figure S1 ). Similar results have been observed in other cyanobacteria like Microcystis aeruginosa , Nostoc muscorum, N. minutum , and Tolypothrix tenuis ( Ferrari et al, 2013 ; Wang et al, 2013 ).…”
Section: Resultssupporting
confidence: 87%
“…As (III) showed more toxicity (~100 times) to Synechocystis cells than As (V) ( Figure 1 , Supplementary Figure S1 ). Similar results have been observed in other cyanobacteria like Microcystis aeruginosa , Nostoc muscorum, N. minutum , and Tolypothrix tenuis ( Ferrari et al, 2013 ; Wang et al, 2013 ).…”
Section: Resultssupporting
confidence: 87%
“…Carotenoids–accessory photosynthetic pigments, are fat-soluble tetraterpenoid molecules that are divided into no oxygen-containing carotenes (β-carotene) and oxygen-containing xanthophylls (lutein, astaxanthin, zeaxanthin) [ 91 ]. Phycobiliproteins are water-soluble proteins that serve as accessory pigments in blue-green or red microalgae, giving a blue (c-phycocyanin, allophycocyanin) [ 34 , 92 ] or pink, red (b-phycoerythrin, c-phycoerythrin) [ 93 , 94 ] colour. Chlorophylls, carotenoids and Phycobiliproteins can find applications in food, cosmetic and pharmaceutical products as coloring, antioxidant, food additive or therapeutic agents [ 95 , 96 , 97 ].…”
Section: Metal Stress As a Methods For Stimulation Of Bioproduct Symentioning
confidence: 99%
“…Also, β-carotene content in Dunaliella salina cells was increased seven times in the presence of 450 µM Fe 2+ and 67.5 mM acetate, however at the expense of four-fold reduction in Dunaliella cell number [ 105 ]. Cyanobacterium Nostoc minutum cultivated photoautotrophically in medium containg 1 g/L arsenic(V) was reported to posses chlorophyll, carotenoid and allophycocyanin content higher by 75%, 40% and 25%, respectively, when compared to control culture [ 34 ]. Similarly, small concentrations of Ni (0.1–10 µM) increased chlorophyll content and c-phycocyanin production even by 47% and up to 4.35 times, respectively, in Anabaena doliolum culture [ 92 ].…”
Section: Metal Stress As a Methods For Stimulation Of Bioproduct Symentioning
confidence: 99%
See 1 more Smart Citation
“…Arsenic (As) is a well-known toxic element naturally present in the Earth's crust [1]. Several studies have shown the different responses of microorganisms exposed to this metal, such as the demethylation process in fungi [2], contamination in food [3], and bioaccumulation, transformation, and release in Microcystis [4].…”
Section: Introductionmentioning
confidence: 99%